Synthesis and Antibacterial activity of Methyl Paraben derivatives (International Journal of Food and Nutritional Sciences, 2022)
: Parabens are class of chemicals widely used as preservatives in the cosmetic and pharmaceutical industries. They are effective preservatives in many types of formulae. These compounds and their salts are used primarily for their bacterial and fungicidal properties. They are also used as food additives. Their analogues viz. ethers and hybrid / fused molecules also possess various biological activities which prompted us to synthesize analogues for their future application as bioactive molecules. All the synthesized compounds were characterized by 1HNMR and mass spectral data and screened for their potential antibacterial activity against Gram + ve and Gram – ve cultures. A Few of them are showing promising antibacterial activity.